Analysis of the Effect of Climate Change on Biodiversity Conditions in West Nusa Tenggara - Jupri, Ahmad; Ahyadi, Hilman; Uzma, Saadatul; Muthma'innah, Elfira; Riski, Tita Nia Ananda; Hakim, Abdurrahman; Wulandari, Suci Yulia; Hidayah, Nurul (Jurnal Biologi Tropis, 2024)
West Nusa Tenggara has a high fauna (animal) characteristic, because its position is on the Wallace Line as an ecological change between the continents of Asia and Australia. Fauna in NTB is spread in various ways according to the existing ecosystem, this happens because there is a match between the type and the environment or place where it develops. An ecosystem that experiences changes in certain conditions can also cause changes in the variety of types. Climate change is one of the causes of changes in an ecosystem. This study aims to determine the impact of climate change on biodiversity conditions in NTB. Research activities were carried out at the NTB Environment and Forestry Service office, the NTB Natural Resources Conservation Center, and the NTB Marine and Fisheries Service, conducted for interviews and data requests regarding climate change and also diversity in NTB. The research method used is purposive sampling. The results of the animal data show that the type already has a small number in NTB so that it must be immediately conserved by the surrounding government so that it does not become extinct due to climate change.